Foundations of Enhanced Problem-Solving Strategies (EPSS): Comprehension Skills and Influence on the Mathematics Performance of Students’ Grade 7 in the Philippines - Recanil, Nelson Jr.; Quirante, Genecelle (Journal of Education and Learning Reviews, 2025)
Background and Aim: Poor reading comprehension is a key factor behind the declining mathematics performance among Filipino students, as effective problem-solving requires understanding concepts, relationships, and word problems in addition to numerical operations. At Liloy National High School, challenges in both comprehension and mathematics have prompted this study to examine how Grade 7 students' skills—remembering, understanding, applying, and analyzing—influence their mathematics performance. Ultimately, the study aims to develop Enhanced Problem-Solving Strategies (EPSS) to bridge comprehension gaps and improve academic outcomes. Materials and Methods: The study employed a descriptive-correlational design involving 127 Grade 7 students. A researcher-made questionnaire, validated by experts and pilot-tested for reliability (Cronbach’s Alpha = 0.710), was used to assess students’ mathematics comprehension levels. At the same time, their academic performance was measured using their mathematics grades. Data were analyzed using statistical tools such as means, frequency counts, and linear regression to elucidate the relationship between comprehension skills and mathematics performance. Results: Results indicated that female students generally demonstrated higher comprehension skills and better mathematics performance than their male counterparts. While females attained “satisfactory” ratings in remembering and understanding, males scored “fairly satisfactory” in these areas; both groups performed similarly in applying and analyzing, albeit at lower levels overall. Linear regression analysis confirmed that comprehension skills significantly influence mathematics performance, thus supporting the formulation of EPSS. Conclusion: In conclusion, the study demonstrates that improved comprehension, particularly higher-order cognitive skills, is associated with enhanced mathematics outcomes, providing a strong basis for adopting EPSS to elevate student performance.